Jacobus Kloppers’ Die Interpretation und Wiedergabe der Orgelwerke Bachs: Två ståndpunkter - Blomberg, Göran; Eppstein, Hans (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1983)
This article consists of two independent contributions for and against some of the theories and methodical guidelines concerning research on and interpretation of J.S. Bach’s nonchorale organ compositions, which are presented by Jacobus Kloppers in Die Interpretation und Wiedergabe der Orgelwerke Bachs. The two authors, Göran Blomberg and Hans Eppstein. particularly discuss Kloppen’ attempts to analyse these compositions on the basis of theories from the baroque period on musical rhetorics.